Assessing Profile and Treatment Outcome in Patients of Ocular Surface Squamous Neoplasia (OSSN) - Shrestha, Eliya; Banstola, Laxman; Maharjan, Indra Man; Gurung, Babita; Gurung, Harimaya; Adhikari, Hari Bikram; Karmacharya, Isha (Nepalese Journal of Ophthalmology, 2019)
Purpose: This study has attempted to assess the profile and treatment outcome of patients with OSSN and report the recurrence rate following treatment of primary OSSN. Materials and Methods: This was a retrospective, non-comparative hospital based observational study. The case files of OSSN patients from Jan 2010 to Dec 2017were assessed. The study site was Himalaya Eye Hospital, Gharipatan, Pokhara. This hospital is the only eye hospital in province 4, Nepal. All the files of suspicious cases of conjunctival mass or OSSN were reviewed. Data regarding demographic characteristics, vision acuity, involved eye, clinical features, conjunctival lesion type, duration of symptoms, preoperative clinical diagnosis, history, other eye disease, associated systemic diseases, occupation as well as treatment modalities of the patients and its outcome were taken. Results: Out of 40 cases, females were 21(52.5%) vesus 19(47.5%) male. Amongthem, 19 patients had keratinized stratified squamous epithelium, 17 had conjunctiva intraepithelial squamous neoplasia and 4 had invasive squalors cell carcinoma. Predominance age group was 15-59 age (25/40, 62.5%), among which 12 had keratinized stratified squamous epithelium, 11 conjunctival intraepithelial squamousneoplasia and 2 had invasive squamous cell carcinoma conjunctival lesion. The mean duration of symptoms was about nine months (S.D. = 5.972). The mean size of lesion mass was 3.28 mm (SD=1.569). More than half of the cases (55%, 22/40) had the mass located at nasal limbus. 95% (38/40) cases underwent lesion total excision and direct closure and 5% (2/40) underwent lesion excision followed by Amniotic Membrane grafting. Only 5% (2/40) cases, those who had undergone lesion excision, the lesion recurrence was observed during follow up period of 31 months. Conclusion: The outcome of the OSSN following the treatment was found to be satisfactory. Further studies with prolonged follow-up are recommended to evaluate the risk of recurrence and other adverse effects.